Alternatively spliced isoforms of WT1 control podocyte-specific gene expression - Lefebvre, Jonathan; Schaefer, Franz (Kidney international, 2015)
The Wilms' tumor suppressor WT1 is a key regulator of podocyte function that is mutated in Denys-Drash and Frasier syndromes. Here we have used an integrative approach employing ChIP, exon array, and genetic analyses in mice to address general and isoform-specific functions of WT1 in podocyte differentiation. Analysis of ChIP-Seq data showed that almost half of the podocyte-specific genes are direct targets of WT1. Bioinformatic analysis further identified coactivator FOXC1-binding sites in proximity to WT1-bound regions, thus supporting coordinated action of these transcription factors in regulating podocyte-specific genes. Transcriptional profiling of mice lacking the WT1 alternative splice isoform (+KTS) had a more restrictive set of genes whose expression depends on these alternatively spliced isoforms. One of these genes encodes the membrane-associated guanylate kinase MAGI2, a protein that localizes to the base of the slit diaphragm. Using functional analysis in mice, we further show that MAGI2{alpha} is essential for proper localization of nephrin and the assembly of the slit diaphragm complex. Finally, a dramatic reduction of MAGI2 was found in an LPS mouse model of glomerular injury and in genetic cases of human disease. Thus, our study highlights the central role of WT1 in podocyte differentiation, identifies that WT1 has a central role in podocyte differentiation, and identifies MAGI2{alpha} as the crucial isoform in slit diaphragm assembly, suggesting a causative role of this gene in the etiology of glomerular disorders.
Gesehen am 16.02.2017